Large scale expression and purification of secreted mouse hephaestin. - Chandrika N Deshpande; Vicky Xin; Yan Lu; Tom Savage; Gregory J Anderson; Mika Jormakka (PLoS ONE, 2017)
Hephaestin is a large membrane-anchored multicopper ferroxidase involved in mammalian iron metabolism. Newly absorbed dietary iron is exported across the enterocyte basolateral membrane by the ferrous iron transporter ferroportin, but hephaestin increases the efficiency of this process by oxidizing the transported iron to its ferric form and promoting its release from ferroportin. Deletion or mutation of the hephaestin gene leads to systemic anemia with iron accumulation in the intestinal epithelium. The crystal structure of human ceruloplasmin, another multicopper ferroxidase with 50% sequence identity to hephaestin, has provided a framework for comparative analysis and modelling. However, detailed structural information for hephaestin is still absent, leaving questions relating to metal coordination and binding sites unanswered. To obtain structural information for hephaestin, a reliable protocol for large-scale purification is required. Here, we present an expression and purification protocol of soluble mouse hephaestin, yielding milligram amounts of enzymatically active, purified protein using the baculovirus/insect cell system.